A Strictly Economic Explanation of Gender Norms: The Lasting Legacy of the Plough - Alessandro Cigno (Institute of Labor Economics (IZA), 2020)
We show that the descendants of ancient farmers may have an interest in marrying among themselves, and thus maintaining the gendered division of labour originally justified on comparative- advantage grounds by the advent of the plough even after they emigrate to a modern industrial economy where individual productivity depends on education rather than physical characteristics. The result rests on the argument that, if an efficient domestic equilibrium requires the more productive spouse to specialize in raising income, and the less productive one in raising children irrespective of gender, this equilibrium will be implemented by a costlessly enforceable contract stipulating that the husband should do the former and the wife the latter, even if individual productivity reflects education rather than gender. Such a contract may not be needed if education and time spent with children give direct utility, because an efficient equilibrium may then be characterized by little or no division of labour.
Keywords: C78; D02; J16; J61; 330; social norm; plough; comparative advantage; matching; migration; hold-up problem